Long-term safety, tolerability, and efficacy of efgartigimod (ADAPT+): interim results from a phase 3 open-label extension study in participants with generalized myasthenia gravis - Howard, James F.; Bril, Vera; Vu, Tuan; Karam, Chafic; Peric, Stojan; De Bleecker, Jan L.; Murai, Hiroyuki; Meisel, Andreas; Beydoun, Said R.; Pasnoor, Mamatha; Guglietta, Antonio; Van Hoorick, Benjamin; et al. (Frontiers in Neurology, 2024)
Objective: ADAPT+ assessed the long-term safety, tolerability, and efficacy of efgartigimod in adult participants with generalized myasthenia gravis (gMG). Methods: ADAPT+ was an open-label, single-arm, multicenter, up to 3-year extension of the pivotal phase 3 ADAPT study. Efgartigimod was administered in treatment cycles of 4 intravenous infusions (one 10 mg/kg infusion per week). Initiation of subsequent treatment cycles was individualized based on clinical evaluation. Safety endpoints included incidence and severity of adverse events. Efficacy endpoints assessed disease severity using Myasthenia Gravis-Activities of Daily Living (MG-ADL) and Quantitative Myasthenia Gravis (QMG) scores. Results: As of January 2022, 151 participants had rolled over to ADAPT+ and 145 had received ≥1 dose of efgartigimod, of whom, 111 (76.6%) were AChR-Ab+ and 34 (23.4%) were AChR-Ab−. Mean study duration (treatment plus follow-up) was 548 days, and participants received up to 17 treatment cycles, corresponding to 217.6 participantyears of exposure. In the overall population, 123 (84.8%) participants reported ≥1 treatment-emergent adverse event; most frequent were headache (36 [24.8%]), COVID-19 (22 [15.2%]), and nasopharyngitis (20 [13.8%]). Clinically meaningful improvement (CMI) in mean MG-ADL and QMG scores was seen as early as 1 week following the first infusion across multiple cycles in AChR-Ab+ and AChR-Ab− participants. Maximal MG-ADL and QMG improvements aligned with onset and magnitude of total IgG and AChR-Ab reductions. For AChR-Ab+ participants at any time point in each of the first 10 treatment cycles, more than 90% had a maximum reduction of ≥2 points (CMI) in MG-ADL total score; across the 7 cycles in which QMG was measured, 69.4% to 91.3% of participants demonstrated a maximum reduction of ≥3 points (CMI) in QMG total score. Many participants demonstrated improvements well beyond CMI thresholds. In AChR-Ab+ participants with ≥1 year of combined followup between ADAPT and ADAPT+, mean number of annualized cycles was 4.7 per year (median [range] 5.0 [0.5-7.6]).